النصوص التشريعية المكتوبة المكرسة لحقوق الانسان في عهد الرسول صلى الله عليه و سلم – وثيقة المدينة انموذج -. (مجلة الواحات للبحوث والدراسات, 2020)
One of the important steps taken by the prophet of god in his construction of the new islamic state in medina is the issuance of a document establishing relations between the new muslim community itself, and between him and the human masses that coexisted in the medina , especially the jews, as it was necessary to organize a relationship between muslims and themselves, and between muslims and other people of the medina, in order to provide security and peace for all people. Key words:   Legislative texts, written, human rights, muhammad the messenger of god , medina document .